2021
DOI: 10.1007/s10681-021-02891-z
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of seed quality and seed germination in two doubled haploid populations of oilseed rape segregating for acid detergent lignin (ADL) content

Abstract: The high lignin content of the seed hull of oilseed rape leads to its black seed color compared to yellow seeded soybean. Reducing lignin and increasing oil and protein content is an important breeding aim in oilseed rape. The objective of the present study was to analyze the inheritance of two rapeseed genetic resources with reduced lignin content in the seeds and to elucidate the effects on seed germination and composition. These resources were crossed to black seeded Express 617 and F1 plants were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In the past, seminal improvements have been made by converting traditional rapeseed to canola or 00‐quality. Efforts in further reducing contents of glucosinolates and bitter taste components as well as improving colour of the oil extracted rapeseed meal and protein are underway (Behnke et al, 2018; Hald et al, 2019; Wanasundara et al, 2016; Widiarsih et al, 2021). For different applications in the food, feed and renewable raw material industry, it would be desirable to have access to already pure raw materials, consisting either of almost pure cruciferin or napin.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, seminal improvements have been made by converting traditional rapeseed to canola or 00‐quality. Efforts in further reducing contents of glucosinolates and bitter taste components as well as improving colour of the oil extracted rapeseed meal and protein are underway (Behnke et al, 2018; Hald et al, 2019; Wanasundara et al, 2016; Widiarsih et al, 2021). For different applications in the food, feed and renewable raw material industry, it would be desirable to have access to already pure raw materials, consisting either of almost pure cruciferin or napin.…”
Section: Discussionmentioning
confidence: 99%
“…Seed damage and oxidative damage can affect oil quality by increasing amounts of reactive oxygen species (ROS) leading to an increased damage of polyunsaturated fatty acids of phospholipids, DNA and proteins (Kumar et al, 2015; Kurek et al, 2019). In two different segregating populations, Widiarsih et al (2021) found that reduced lignin content in the seed coat was accompanied by increased bacterial and fungal growth around germinating seeds on moist filter paper and that this may affect seed germination and seed longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the seed lignin content can be achieved by increasing the seed size for a better embryo to seed coat proportion and by reducing the seed coat thickness through decreased lignin deposition in the seed coat (Carré et al, 2016; Dimov et al, 2012; Wittkop et al, 2009). Although a large number of quantitative trait loci (QTL) for reduced seed lignin content on different chromosomes of the oilseed rape A and C genome have been published (Badani et al, 2006; Behnke et al, 2018; Liu et al, 2012; Miao et al, 2019; Stein, 2013; Widiarsih et al, 2021), only little progress in further evaluation of the mentioned plant material has been made, and yet there is no competitive, yellow‐seeded oilseed rape cultivar on the market (Rahman & McVetty, 2011; Simbaya et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Low lignin content in the seed coat is correlated with high oil content [140]. SNP analysis indicated a narrow genomic region for low lignin content [141].…”
Section: Seed Traitsmentioning
confidence: 99%